Comparative evaluation of efficacy of guided endodontic technique with and without sleeve for access cavity preparation: An In Vitro study - Varun Prabhuji; S. Archana; A. Srirekha; Veena Pai; C. Champa; Ashwija Shetty (Elsevier, 2024)
Background: Calcific metamorphosis in root canals is common and presents challenges in gaining access. Guided endodontics offers a solution to overcome these difficulties. The PriciGuide® system is a patented guided endodontic technique claiming superior precision compared to sleeve-based guides. This study aims to compare deviation between the PriciGuide® system and the guide with sleeve. Methods: A patient with calcified canal underwent CBCT scanning to obtain a DICOM file. Using the DICOM file, 3D models were printed. The patient's cast was scanned to obtain an STL file. Using DICOM and STL files, the guide with sleeve was designed using BlueSkyBio software and 3D printed. The PriciGuide® system was obtained from Roots to Cusps® Private Limited. Access opening was performed using conventional method, guide with sleeve and guide without sleeve (PriciGuide® system).Samples underwent radiograph scans to measure coronal, apical, and angular deviations, as well as procedural time. Results: One-Way ANOVA and Post Hoc Bonferroni's test revealed that coronal, apical, and angular deviations were lowest in the guide without sleeve group. However, access opening times were similar in both guided technique groups. Conclusions: The PriciGuide® system offers precise access cavity preparation for calcified canals, showing minimal deviation compared to the sleeve-based guides. It facilitates accurate root canal access regardless of the dentist's experience level. This study utilized 3D-printed teeth that do not fully replicate the complexities of natural teeth, further research is needed to validate the PriciGuide® system's performance on natural teeth and assess deviation using CBCT for a more comprehensive evaluation.